2009
DOI: 10.1097/wnp.0b013e3181c298c9
|View full text |Cite
|
Sign up to set email alerts
|

Very High-Frequency Oscillations (Over 1000 Hz) of Somatosensory-Evoked Potentials Directly Recorded From the Human Brain

Abstract: The aims of this study were to record high-frequency oscillations (HFOs) associated with somatosensory-evoked potentials from subdural electrodes and to investigate their generators and clinical significance. Six patients who underwent long-term subdural electrode monitoring were studied. Somatosensory-evoked potentials were recorded directly from the subdural electrode after stimulation of the median nerve. Bandpass filter was 10 to 10,000 Hz for conventional somatosensory-evoked potential and 500 to 10,000 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 36 publications
1
20
1
Order By: Relevance
“…In comparison to controls, migraine subjects had a significantly higher likelihood of activation in the SMA and the occipital and ipsilateral sensorimotor cortices. There are reports showing that the brain generates signals around 2,632 Hz in the somatosensory cortex 28 and 2,500 Hz in the epileptic regions. 32 However, those previous reports are based on invasive intracranial recordings and are limited to patients with intractable epilepsy who are surgical candidates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In comparison to controls, migraine subjects had a significantly higher likelihood of activation in the SMA and the occipital and ipsilateral sensorimotor cortices. There are reports showing that the brain generates signals around 2,632 Hz in the somatosensory cortex 28 and 2,500 Hz in the epileptic regions. 32 However, those previous reports are based on invasive intracranial recordings and are limited to patients with intractable epilepsy who are surgical candidates.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recent invasive recordings have shown that a brain with epilepsy generates very-high-frequency activation near 2,632 Hz. 28,32 The examination of high-frequency brain activation may have the potential to provide key information about cortical dysfunction in migraine.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, when utilizing low-noise EEG amplifiers an increase in single-trial hf-EEG power coinciding with the σ-burst in the averaged hf-SEP could be demonstrated , while a previous study with conventional EEG amplifiers failed to demonstrate this increase of single-trial hf-EEG power (Valencia et al, 2006). Furthermore, hf-SEP components at approximately 950 Hz were discovered in non-invasive surface EEG (Scheer et al, 2011;Fedele et al, 2012), previously attainable only by the use of implanted deep electrodes in the thalamus of patients with Parkinson's disease (Klostermann et al, 2002) or subdural recordings (Sakura et al, 2009).…”
Section: Introductionmentioning
confidence: 90%